Analysing language errors in final examination papers in Universiti Teknologi MARA / Kamisah Ariffin, Rahimah Abd Wahab and Jun Nirlawati Mohd Sahidol - Ariffin, Kamisah; Abd Wahab, Rahimah; Mohd Sahidol, Jun Nirlawati (2011)
Studies on errors in examination papers have been scarce. Perhaps, this is due to the assumption that examination papers would have gone through a stringent series of editing and proofreading before they can be approved. However, the occurrence of language related errors such as lexical and syntactical errors in some of the final examination papers in Universiti Teknologi MARA has shown that such assumption is wide off the mark. The analysis of the present study shows that language errors were found extensively in the final examination papers examined. From the total of 916 papers from 22 faculties, 465 were found to contain language errors ranging from punctuation to sentence structure. The findings of this study have raised some legitimate concerns for the quality improvement of the final examination papers in UiTM. Some recommendations are put forward that require concerted efforts from the test setters themselves and the university’s examination unit in ensuring that examination papers are free from language errors.